Artificial intelligence driven robotic control system for personalized elderly care and foot massage - Bhatlawande, Shripad; Shilaskar, Swati; Akotkar, Soham; Joshi, Anish; Ansari, Zayd (International Journal of Reconfigurable and Embedded Systems (IJRES), 2025)
This research presents an electronic system for providing foot massage to the elderly, along with artificial intelligence (AI) driven voice-controlled conversation bot. The problem under study focuses on the elderly age group suffering from foot related ailments, most commonly foot pain. Also, the risk of depression or anxiety is high for this age group due to social isolation. These problems are addressed by the system under discussion integrated with a voice assistant to converse with the elderly. The AI assisted conversation bot enables the elderly to make customized reminders for their timely medications and provides general updates on essential topics. The system extends to provide the elderly, foot, and calf massage controlled with mobile application. It consists of a low power motor arrangement along with a high computing system. The electronic system was subjected to trials on elderly for verification and validation of the system to assess its ability of providing users with appropriate assistance. The trials were conducted on twenty elderly, aged sixty, and above, living self-sufficiently with foot related ailment. All elderly were subjected to the conversation bot along with the foot and calves’ massage, providing subjective feedback on the system's ability to enhance their quality of life. The subjective feedback after quantification have demonstrated the ability of the system in improving their living standards.